Digital Promotions Campaign Increases SNAP Participation at New England Farmers' Markets: A Randomized Controlled Trial. (7th June 2021) - John, Sara; Rivera, Gabrielle; Cash, Sean; Economos, Christina; Rimm, Eric; Wilde, Parke
Abstract: Objectives: Greater number and increased frequency of farmers' markets are an important strategy to improve community-level diet quality by increasing fruit and vegetable availability, yet fall short of addressing health disparities due to a predominantly affluent, white clientele. Introducing Supplemental Nutrition Assistance Program (SNAP) financial incentives at farmers' markets increases patronage and sales amongst people with economic disadvantage, however SNAP participant incentive program awareness and farmers' market sales remain low. This study examined whether a digital campaign promoting SNAP incentive programs increases farmers' market SNAP participation. Methods: This study was a parallel RCT, with randomization of zip codes to receive ( a ) digital promotions or ( b ) no additional promotions. The study sample included target zip codes ( n = 96) near New England farmers' markets with SNAP incentive programs ( n = 23). The intervention was a 13-week campaign, placing digital ads on Facebook and the Fresh EBT app promoting SNAP incentive program savings at farmers' markets. The study measured farmers' market SNAP shopping patterns and sales as well as digital campaign delivery and engagement. Data were collected July 1 – September 30, 2020. Results: The digital campaign reached 251, 966 people, generated 2 million impressions, and resulted in 12, 849 clicks. During Summer 2020, zip codes randomized to receive digital promotions had 33.1 SNAP transactions (SE: 6.9) and control zip codes had 18.1 transactions (SE: 4.3), or 82% more transactions associated with promotions ( P = 0.068). There were also more new customers from promotion zip codes (10.8 [SE = 2.5] customers) than control zip codes (5.7 [SE = 1.4] customers), or 90% more new customers ( P = 0.075). SNAP and incentive sales were higher from promotion zip codes (1392 [SE: 306]) than control zip codes (949 [SE: 273]), or 47% greater ( P = 0.284), but sales differences were not statistically significant unless controlling for Summer 2019 farmers' market sales. Conclusions: Digital SNAP incentive program promotions can increase farmers' market SNAP participation, the primary study outcome, leveraging SNAP to expand farmers' market reach and associated nutrition benefit to historically marginalized populations. Funding Sources: USDA Food Insecurity Nutrition Incentives Program.